(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Many clinical aspects of women during menopause, such as psychological, physiological changes may influence quality of life. Menopause occurs typically between ages 45 and 55 years of age and is associated with hormonal changes, including a reduction of estrogen hormone and increase in follicle stimulating hormone. This hormone shift may lead to an increased risk of type 2 diabetes mellitus, osteoporosis, heart disease, metabolic syndrome, fatty liver diseases etc. Menopause is a natural biological process that progress with aging and it is characterized by the complete stop of the menstrual cycle resulting from the cessation of ovarian function. Phytoestrogens are natural compounds derived from plants; they offer potential benefits for females in reducing menopausal symptoms. The primary objective of this review paper is to compile literature on menopause, with a focus on the factors that influence menopausal health in both positive and negative way. A number of studies have found a link between menopausal symptoms and quality of life in women. Lifestyle modifications such as dietary interventions, play a significant role in the prevention of CVD, Diabetes, Osteoporosis etc. Depending on today’s living and poor dietary habits, women have focused on the efforts to protect or improve their health status, especially due to intense work pace and increased poor eating habits.